Antibacterial Activity of Gyrinops versteegii Fruit Extracts against Staphylococcus aureus and Escherichia coli and GC-MS Analysis - Ernin Hidayati; Yuli Handayani; I Made Sudarma (Journal of Mathematical and Fundamental Sciences, 2022)
Gyrinops versteegii is widely used in the perfume, incense, and cosmetic industries as a raw material. Other potential uses of the plant are being explored, including in food and medicine. Therefore, this study carried out antibacterial assay and gas chromatography-mass spectroscopy of G. versteegii fruit extracts in three solvents with different polarities, i.e., n-hexane, dichloromethane, and methanol. The agar well diffusion method was then used to test the extracts against Staphylococcus aureus and Escherichia coli. The dichloromethane extract showed the most effective antibacterial activity against S. aureus at a concentration of 40%, with a zone of inhibition of 13.17 mm compared to E. coli, for which it was 7 mm. Furthermore, the bacterial species showed different responses to the extracts. Total and partial inhibition was shown by the G. versteegii fruit extracts against S. aureus and E. coli, respectively. Furthermore, GC-MS identified the following compounds in G. versteegii fruit extract: palmitic, oleic, and stearic acid, as well as bis-(2-ethylhexyl) phthalate, 2,3-dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one, methyl octadec-9-enoate, squalene, and 2-monopalmitin derivates. The results showed antibacterial potency of G. versteegii fruit extract against pathogenic bacteria. Additionally, the antibacterial activity of the extract was stronger against S. aureus compared to E. coli.